Analysis Identity Fusion and Psychosocial Development: How the Role of Father, Mother and Son on Radicalization within Family - Zuhdi, Muhammad Luthfi; Syauqillah, Muhamad (Journal of Strategic and Global Studies, 2020)
One of crucial issues of radicalism lately is the involvement of family members in acts of terrorism. One of those interesting case is the case of Dita Oepriyanto’s family, the perpetrator of suicide bombing in one church in Surabaya, East Java. Family involvement in extremist acts and terrorism in Indonesia is not a new thing, the story of Dita Oeprianto is a historical cycle with different shifting actors. The story of the Leader of Darul Islam, RM. Kartosuwiryo who rebelled against the Indonesian republic accompanied by his wife and wife giving birth to children in the forest can be seen in the perspective of family involvement, as well as several Afghan alumni figures. The cycle also happened to the derivative organization from Darul Islam which transformed into combatants in Afghanistan, then moved to Jamaah Islamiyah. Changes occur during the ISIS conflict, family factors are not the main cause of joining a person with a terror organization, there are media factors that make individuals join. This study analyzes the involvement of families in the extremism movement and acts of terror by using the qualitative method, with sources of literature and interviews with Afghan alumni, former prisoners and prisoners of terrorism cases. The theory used to analyze facts and data is identity fusion and psychosocial development. The results of the study concluded that all elements of the family (children, wife, husband, grandfather, grandmother, and relatives) were very susceptible to the potential of being exposed to radicalism.